In-brace alterations of pulmonary functions in adolescents wearing a brace for idiopathic scoliosis. (August 2019) - Yagci, Gozde; Demirkiran, Gokhan; Yakut, Yavuz
Background: Despite the common use of braces to prevent curve progression in idiopathic scoliosis, their functional effects on respiratory mechanics have not been widely studied. Objective: The objective was to determine the effects of bracing on pulmonary function in idiopathic scoliosis. Methods: A total of 27 adolescents with a mean age of 14.5 ± 1.5 years and idiopathic scoliosis were included in the study. Pulmonary function evaluation included vital capacity, forced expiratory volume, forced vital capacity, maximum ventilator volume, peak expiratory flow, and respiratory muscle strengths, measured with a spirometer, and patient-reported degree of dyspnea. The tests were performed once prior to bracing and at 1 month after bracing (while the patients wore the brace). Results: Compared with the unbraced condition, vital capacity, forced expiratory volume, forced vital capacity, maximum ventilator volume, and peak expiratory flow values decreased and dyspnea increased in the braced condition. Respiratory muscle strength was under the norm in both unbraced and braced conditions, while no significant difference was found for these parameters between the two conditions. Conclusion: The spinal brace for idiopathic scoliosis tended to reduce pulmonary functions and increase dyspnea symptoms (when wearing a brace) in this study. Special attention should be paid in-brace effects on pulmonary functions in idiopathic scoliosis. Clinical relevance: Bracing seems to mimic restrictive pulmonary disease, although there is no actual disease when the brace is removed. This study suggests that bracing may result in a deterioration of pulmonary function when adolescents with idiopathic scoliosis are wearing a brace.